1996
DOI: 10.1113/jphysiol.1996.sp021235
|View full text |Cite
|
Sign up to set email alerts
|

Differential oxygen sensitivity of calcium channels in rabbit smooth muscle cells of conduit and resistance pulmonary arteries.

Abstract: 1. Calcium currents were recorded from smooth muscle cells dispersed from conduit and resistance rabbit pulmonary arteries. We tested the hypothesis that Ca2+ channel activity was regulated by environmental 02 tension.2. Conduit (proximal) and resistance (distal) myocytes differ in their Ca2P channel density and responses to low Po2. Ca2P current density in distal myocytes (20'7 + 7-4 pA pFY, n = 10)is almost twice the value in proximal myocytes (12-6 + 5-5 pA pF', n = 39). In proximal myocytes, the predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 18 publications
2
57
2
1
Order By: Relevance
“…In our (53)(54)(55) previous studies of distal PASMC, nifedipine, an antagonist of L-type Ca 2ϩ channels, inhibited VOCE (11) and/or causing membrane depolarization (25,31,40,61). The former was reported in rabbit distal PASMC (11); however, this observation remains unconfirmed and its underlying mechanism unknown.…”
Section: Discussionmentioning
confidence: 88%
“…In our (53)(54)(55) previous studies of distal PASMC, nifedipine, an antagonist of L-type Ca 2ϩ channels, inhibited VOCE (11) and/or causing membrane depolarization (25,31,40,61). The former was reported in rabbit distal PASMC (11); however, this observation remains unconfirmed and its underlying mechanism unknown.…”
Section: Discussionmentioning
confidence: 88%
“…Our experiments were also performed in the absence of extracellular Ca2 , thereby obviating the possibility of depolarization being mediated as a consequence of Ca2+ influx through voltage-activated Ca2+ channels. This is an important consideration since pulmonary arterial Ca2+ channels are known to be activated by hypoxia (Franco-Obreg6n & L6pez-Barneo, 1996), an effect which could account at least in part for the depolarization seen by others (Post et al 1992;Yuan et al 1993). Finally, no other studies have used cells isolated from small pulmonary arterial vessels.…”
Section: Synergism Between Depolarization and Hypoxiamentioning
confidence: 99%
“…Using whole cell patch-clamp technique, Franco-Obregon and coworkers (27,28) showed that rabbit PASMC voltage-gated Ca 2ϩ channels opened and closed by alternating a hypoxia-reoxygenation stimulus, respectively. They also demonstrated that resistance and conduit PASMC voltage-gated Ca 2ϩ channels were opened and closed by exposure to reductions in PO 2 (26), thus indicating that either the expression or regulation of L-type Ca 2ϩ channels was different in conduit arteries that show minimal contraction to hypoxia compared with resistance pulmonary artery smooth muscle that generally contract to hypoxia. Additionally, some of the latest data also suggest that hypoxia stimulates opening of receptor-operated Ca 2ϩ channels and modulates Ca 2ϩ release from the ryanodinesensitive Ca 2ϩ stores that mediate HPV (76).…”
Section: ؉mentioning
confidence: 99%